Analisis Penggunaan Metode Tabarak dalam Menghafal Al-Qur’an Juz 30 di Markaz Tahfidz Balita Raudhatu Tilawatil Qur’an Dumai - Sheila Mudina; Miftahirrizqa; Risnawati (NANAEKE: Indonesian Journal on Early Childhood Education, 2022)
The purpose of this study was to determine the implementation of the Tabarak Method in memorizing the Qur'an in Mataba Raudhatu Tilawtil Qur'an Dumai, as well as to determine the inhibiting and supporting factors in implementing the Tabarak Method in Mataba Raudhatu Tilawatil Qur'an Dumai. This study uses descriptive qualitative methods with data collection techniques in the form of interviews, observation, and documentation. The source of data comes from teachers as many as 2 people guiding the Tabarak method at the institution. Data analysis uses the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The research findings provide the following explanation: 1) In Mataba Raudhatu Tilawatil Qur'an Dumai, learning activities using the Tabarak method to memorize the Koran are led by the school principal and teachers who have attended several special trainings related to learning using the Tabarak method. The rote muraja'ah routine is followed by murattal audio in the form of MP3s which have been distributed to each santri. This media can also be used for muraja'ah activities at home with parents of students, and activities at this school also use other learning media such as; Speakers, Television, and others; 2) the supporting factors in the implementation of this learning are the role of the teacher as a fun educator for children who also have good tahsin and mastery of memorization, adequate facilities, and good cooperation from student parents and teachers in memorizing the Al Quran; 3) The inhibiting factors for this activity are the lack of focus of the child due to the child playing in class, the child being late or not coming to school, the lack of supervision of the student's guardian due to busyness outside the home, and there are still teachers who are not licensed. These findings have implications, indicating that student learning systems must be strengthened by school administrators and implementation teams. Teachers are also required to improve parenting skills and use creative and innovative learning strategies.